PENGARUH KEDISIPLINAN, MOTIVASI DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PERAWAT RUMAH SAKIT PETALA BUMI PEKANBARU - Nurul Fajri; Jumiati Sasmita; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to analyze the influence of variables Discipline, motivation and the Physical Environment on Performance. Research was conducted on Nurses, Hospitals Petala Bumi in Pekanbaru. In this research consists of four variables: the dependent variable and three independent variables. These variables are Performance (Y), the Physical Environment (X3), Motivation (X2), and Discipline (X1). This study was conducted using a sample of 86 people. This research using purposive sampling technique is the determination of the sample is based on respondents who have certain criteria to fill out a questionnaire. In terms of data analysis, this study using multiple regression analysis using SPSS (Statistical Package for Social Science) version 20. Based on the hypothesis tests conducted, results indicate that the Disciplinary research and significant positive effect on performance, motivation positive and significant impact on the Performance and Physical Environment positive and significant impact on performance. Discipline, Motivation and Work Environment Physical positive and significant impact on Performance.Keywords: Discipline, Motivation, Physical Environment, Performance.